Novel connections and gaps in ethylene signaling from the ER membrane to the nucleus - Cho, Young-Hee; Yoo, Sang-Dong (Frontiers in Plant Science, 2015)
The signaling of the plant hormone ethylene has been studied genetically, resulting in the identification of signaling components from membrane receptors to nuclear effectors. Among constituents of the hormone signaling pathway, functional links involving a putative MAPKK kinase CTR1 and a membrane transporter-like protein EIN2 have been missing for a long time. We now learn that EIN2 is cleaved and its C-terminal end moves to the nucleus upon ethylene perception at the membrane receptors, and then the C-terminal end of EIN2 in the nucleus supports EIN3-dependent ethylene-response gene expression. CTR1 kinase activity negatively controls the EIN2 cleavage process through direct phosphorylation. Despite the novel connection of CTR1 with EIN2 that explains a large portion of the missing links in ethylene signaling, our understanding still remains far from its completion. This focused review will summarize recent advances in the EIN3-dependent ethylene signaling mechanisms including CTR1-EIN2 functions with respect to EIN3 regulation and ethylene responses. This will also present several emerging issues that need to be addressed for the comprehensive understanding of signaling pathways of the invaluable plant hormone ethylene.